(untitled) (Research, Society and Development, 2022)
The article aims to analyze the contributions of the Project Model Canvas in the planning of teachers’ continuing education. In this context, it specifically addresses how to use the Project Model Canvas - PMC for project development, which should be considered when planning teacher training and the contributions of this instrument to this planning. Bibliographic research was used to base the study, followed by the application of a questionnaire with the Training Director of the municipality of Caucaia-CE. It was concluded that the PMC can effectively contribute to the planning of continuing education for teachers, as it allows the systematic observation of all the elements necessary for the training meeting to take place without intercurrences.